PERSEPSI WANITA KARIR TERHADAP OBESITAS DI KOTA BIMA NUSA TENGGARA BARAT: PERSEPSI WANITA KARIR TERHADAP OBESITAS DI KOTA BIMA NUSA TENGGARA BARAT - Zahratul Hayati (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
Obesity is an epidemic that poses the biggest global public health challenge and ranks among the top three causes of chronic health disorders. WHO has set a target in 2025 to maintain the prevalence of obesity back to 2010 figures. Overweight and obesity are the causes of population death in various countries in the world. However, obesity can be prevented. Several factors cause obesity besides genetics, overeating and lack of activity patterns. It is suspected that there is a misperception, especially women who are obese, so that it has an impact on the regulation of diet and activity patterns. The purpose of this study was to explore the perceptions of career women regarding obesity. This study used a qualitative method with in-depth interviews with mothers, homeroom teachers, UKS teachers and health service officers. Observation of work and home environment, career woman. By using a health belief model theory approach that can help explain the perceptions held by career women. These perceptions include perceptions of the severity of a disease (perceived severity), perceptions of susceptibility (perceived susceptibility), perceptions of benefits (perceived benefits), perceptions of barriers (perceived barriers), prerequisites for taking action (cues to action), and self-efficacy. By knowing these perceptions, it will be known the factors that can influence people's behavior in an effort to prevent obesity in career women. This research is a qualitative research. conducted in the City of Bima, NTB. It is hoped that this research will be able to explore and understand the meaning obtained from the informants from the experiences conveyed by the informants at the research location. Data collection techniques were carried out by in-depth interviews and observations. The data analysis used in this research is content analysis. The data validity strategy that will be applied in this study is to triangulate data sources by member checking to clarify the results of the interviews. In addition, peer review/peer debriefing was conducted. The data validity strategy that will be applied in this study is to triangulate data sources by member checking to clarify the results of the interviews. In addition, peer review/peer debriefing was conducted. The data validity strategy that will be applied in this study is to triangulate data sources by member checking to clarify the results of the interviews. In addition, peer review/peer debriefing was conducted. Some misperceptions in career women that result in errors in regulating diet and activities that trigger obesity include informants who think it is natural that women with income will become fat because they are able to consume their favorite foods at any time, if there are many office activities causing thinness with itself. The informants thought that local foods such as offal, soto, satay, curry, meatballs, and chicken noodles because they were processed by local residents were not fast food. Informants think that skipping lunch is a diet to lose weight. Informants think that office activities can be a substitute for sports because they think they are tired with a busy schedule at work.